2018
DOI: 10.1039/c7lc01283g
|View full text |Cite
|
Sign up to set email alerts
|

Inertial manipulation of bubbles in rectangular microfluidic channels

Abstract: Inertial microfluidics is an active field of research that deals with crossflow positioning of the suspended entities in microflows. Until now, the majority of the studies have focused on the behavior of rigid particles in order to provide guidelines for microfluidic applications such as sorting and filtering. Deformable entities such as bubbles and droplets are considered in fewer studies despite their importance in multiphase microflows. In this paper, we show that the trajectory of bubbles flowing in rectan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 47 publications
2
41
0
Order By: Relevance
“…It has been demonstrated that nucleation rate (frequency of bubble production) and the volume of the detaching bubbles show a non-linear dependence on the shear rate, in particular, higher flow rates over artificial nucleation sites lead to detachment of smaller gas bubbles. 100,162 This general and intuitive behavior was also observed in a micro-electrolyzer for water splitting. 163 It was also observed that with increased applied voltage, the bubbles detach at smaller radii, attributed to the influence of convection induced by detaching bubbles and electrostatic repulsions between the bubbles and the electrode.…”
Section: Flow Fieldssupporting
confidence: 59%
“…It has been demonstrated that nucleation rate (frequency of bubble production) and the volume of the detaching bubbles show a non-linear dependence on the shear rate, in particular, higher flow rates over artificial nucleation sites lead to detachment of smaller gas bubbles. 100,162 This general and intuitive behavior was also observed in a micro-electrolyzer for water splitting. 163 It was also observed that with increased applied voltage, the bubbles detach at smaller radii, attributed to the influence of convection induced by detaching bubbles and electrostatic repulsions between the bubbles and the electrode.…”
Section: Flow Fieldssupporting
confidence: 59%
“…In the case of a neutrally buoyant rigid particle suspended in a Newtonian fluid, the particle migration and final equilibrium position are determined by two opposing forces acting on the particle: these forces are the wall induced lift force that pushes the particle away from the wall and the shear-gradient induced lift force that drives the particle towards the wall, the latter resulting from the rigid particle resistance to deformation [28,64]. When the particle is deformable, its dynamics is further complicated by the additional force originating from the particle shape deformation, which depends on the elastic properties of the material (e.g., the elastic modulus G) [30,31]. Note that, the particle deformation also affects and modifies the other two forces.…”
Section: Resultsmentioning
confidence: 99%
“…This framework was developed by Balestra et al (2018) and has been well validated against the classical theory (Bretherton 1961). For more details, refer to Balestra et al (2018) and Hadikhani et al (2018).…”
Section: Experimental Set-up and Numerical Methodsmentioning
confidence: 99%